2015
DOI: 10.1007/s00063-015-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

Adäquate Volumensubstitution bei septischem Schock unter hohen Katecholamindosen

Abstract: It is possible to wean a substantial proportion of septic shock patients from high-dose catecholamines in combination with a needs-adapted forced volume challenge test. The importance of appropriate fluid loading prior to the use of high catecholamine doses should be a main subject of discussion in patients with severe septic shock and was confirmed in this study. This should be oriented to clinical and if possible, hemodynamic parameters and should not be underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…When considering fluid balance with correlation analysis, we found that lower reductions, which might be indicative of a less effective response to hemoadsorption but also caused by various other factors in the clinical course of the patient, were associated with almost constant norepinephrine requirements and a higher treated blood volume, suggesting that, despite fluid resuscitation and hemoadsorption therapy, vasopressor demands remained worse. In this regard, Lewejohanns and colleagues described the importance of appropriate fluid loading prior to the use of high catecholamine doses and on the influence of catecholamine demand [ 29 ]. This essentially means that if the effect on catecholamine demand is absent despite fluid resuscitation and if the fluid balance remains high, that the endothelium remains permeable and a potential positive effect of hemoadsorption is not present in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…When considering fluid balance with correlation analysis, we found that lower reductions, which might be indicative of a less effective response to hemoadsorption but also caused by various other factors in the clinical course of the patient, were associated with almost constant norepinephrine requirements and a higher treated blood volume, suggesting that, despite fluid resuscitation and hemoadsorption therapy, vasopressor demands remained worse. In this regard, Lewejohanns and colleagues described the importance of appropriate fluid loading prior to the use of high catecholamine doses and on the influence of catecholamine demand [ 29 ]. This essentially means that if the effect on catecholamine demand is absent despite fluid resuscitation and if the fluid balance remains high, that the endothelium remains permeable and a potential positive effect of hemoadsorption is not present in these patients.…”
Section: Discussionmentioning
confidence: 99%